Utilidad hipnoparto como estrategia no farmacológica para el manejo del dolor en el trabajo de parto (2022)
At present, several women have fears or fears related to labor and/or childbirth, since they often relate it to painful experiences, which they have heard from their families or have personally experienced, which is why it is essential to know non-pharmacological techniques, used to help improve the labor experience. Due to the above, a review of the literature on hypnobirthing was carried out that aims to show with evidence, the benefits that this strategy brings and thus be able to make its successful use visible in other countries, since at present the subject is little known both by the health personnel and pregnant women and its implementation could make pregnant women have a positive experience in this process.